Optimization of milling holes process parameters for carbon fiber reinforced composites based on cryogenic cooling - Wang, Fengbiao; Cao, Lihua (Machining science and technology, 2025)
The cryogenic cooling method of liquid nitrogen (LN 2 ) spray is often adopted to effectively inhibit the delamination defects in the hole-making process of carbon fiber-reinforced composites (CFRP). But optimizing the processing parameters including cooling temperature, radial feed, milling speed, axial feed and nozzle angle is necessary. Therefore, the analysis method of variance was employed. A series of milling hole experiments were carried out at different temperature strategies. The results show that the LN 2 cryogenic cooling method can achieve the high-quality and efficient cryogenic cooling milling hole compared with the conventional dry one, and the delamination defect has been greatly improved. Through processing parameter optimization range and significance analysis, the influence order is the cooling temperature, axial feed, nozzle angle, radial feed and milling speed. Meanwhile, the value of each influence factor is the cooling temperature of −170 °C, the axial feed of 30 mm/min, the nozzle angle of 36.5°, the radial feed of 100 mm/min and the cutting speed of 250 m/min. And the actual processing result is f d = 1.023. Although it is slightly larger than the predicted value f d = 1.016, near 50% milling efficiency is increased. Furthermore, lowering the cryogenic cooling temperature will affect the binding strength of the fiber and the resin matrix and lead to the delamination of the hole outlet. A suitable LN 2 jet angle is a necessary condition for effective cooling temperature. The research results can be used as a reference for obtaining high- quality milling hole technology at cryogenic cooling for fiber-reinforced composites.